LSSR KGB investigation izolator 1959–1991 - Žiūkas, Mindaugas (Genocidas ir rezistencija, 2025)
The aim of the thesis is to reveal the activities of the interrogation detention facility in the semi–basement of the LSSR’s KGB building. The article focuses on the working methods used by the KGB, the staff of the detention facility, the holding of detainees in the cells, the conditions of detention, the rights of the detainees and the technical parameters of the detention facility. Without going into the personalities of the detainees and the prisoners, the thesis analyses the types of crimes for which citizens of the LSSR (and not only) were imprisoned in the KGB interrogation detention facility.